The effect of the gap between screw and cylinder on the operating characteristics injection molding machine - Матвіїшин, П.В. (Problems of Tribology, 2016)
The experiment also showed the dependence of the twister and the time of loading and damping different types of plastic on the size of clearance between the screw and the cylinder, determined critical data for the clearance between the screw and the cylinder for the plastic under study. The excess of critical data makes the quality of the product worse.